2015
DOI: 10.2147/ndt.s79444
|View full text |Cite
|
Sign up to set email alerts
|

Decreased serum levels of brain-derived neurotrophic factor in schizophrenic patients with deficit syndrome

Abstract: BackgroundBrain-derived neurotrophic factor (BDNF) is a well-established neurotrophin that plays a role in the pathophysiology of numerous psychiatric disorders. Many studies have investigated the serum BDNF levels in patients with schizophrenia. However, there are restricted data in the literature that compare the serum BDNF levels in patients with deficit and nondeficit syndromes. In this study, we aimed to compare the serum BDNF levels between schizophrenic patients with deficit or nondeficit syndrome and h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 59 publications
2
8
0
Order By: Relevance
“… 47 We recently showed significantly decreased BDNF levels in patients with DS when compared with HC. 48 Thus, our two previous studies indirectly supported the hypothesis of an increased apoptotic mechanism in DS patients. In the present study, we demonstrated increased levels of apoptosis in patients with DS when compared with the NDS and HC groups.…”
Section: Discussionsupporting
confidence: 73%
“… 47 We recently showed significantly decreased BDNF levels in patients with DS when compared with HC. 48 Thus, our two previous studies indirectly supported the hypothesis of an increased apoptotic mechanism in DS patients. In the present study, we demonstrated increased levels of apoptosis in patients with DS when compared with the NDS and HC groups.…”
Section: Discussionsupporting
confidence: 73%
“…However, clinical investigations of BDNF in psychiatric disorders is contradictory. Some reports have stated reduced blood BDNF levels in patients with SCZ ( Yang et al, 2011 ; Akyol et al, 2015 ; XY Zhang et al, 2015 ), BD ( Machado-Vieira et al, 2007 ; de Oliveira et al, 2009 ), and MDD ( Sen et al, 2008 ; Bocchio-Chiavetto et al, 2010 ; Polyakova et al, 2015 ), whereas others have confirmed opposite findings ( Durany et al, 2001 ; Jevtović et al, 2011 ; Munkholm et al, 2014 ). Nevertheless, some meta-analysis of case-control studies examined changes in BDNF following pharmacologic treatment in psychiatric disorders ( Goldstein and Young, 2013 ; Pagsberg et al, 2014 ; Yan et al, 2014 ).…”
Section: Biomarker Discovery Researchmentioning
confidence: 98%
“…A number of preclinical studies have also suggested that the brain-derived neurotrophic factor (BDNF), a well-established neurotrophin, plays an important role in the pathophysiology of numerous psychiatric disorders ( Teche et al, 2013 ; Munkholm et al, 2014 ; Akyol et al, 2015 ) and regulates neuronal growth, survival, and function of the adult brain ( Yukimasa et al, 2006 ; Calabrese et al, 2014 ). However, clinical investigations of BDNF in psychiatric disorders is contradictory.…”
Section: Biomarker Discovery Researchmentioning
confidence: 99%
“…There is mounting evidences that DS may be a distinct subtype of schizophrenia, which may help to reduce the heterogeneity of this disease. Akyol et al reported that the serum BDNF levels in DS were significantly lower than those in the healthy individuals, while those in NDS patients were similar to normal levels [19]. In contrast, Valiente-Gómez et al did not find any significant differences across the three groups [20].…”
Section: Introductionmentioning
confidence: 99%